Clinical progress of anti-angiogenic targeted therapy and combination therapy for gastric cancer - Xu, Donghan; Luo, Yehao; Wang, Peng; Li, Jiaxin; Ma, Linrui; Huang, Jie; Zhang, Hao; Yang, Xiaoman; Li, Liqi; Zheng, Yuhong; Fang, Gang; Yan, Peiyu (Frontiers in Oncology, 2023)
The incidence of gastric cancer is increasing year by year. Most gastric cancers are already in the advanced stage with poor prognosis when diagnosed, which means the current treatment is not satisfactory. Angiogenesis is an important link in the occurrence and development of tumors, and there are multiple anti-angiogenesis targeted therapies. To comprehensively evaluate the efficacy and safety of anti-angiogenic targeted drugs alone and in combination against gastric cancer, we systematically searched and sorted out relevant literature. In this review, we summarized the efficacy and safety of Ramucirumab, Bevacizumab, Apatinib, Fruquintinib, Sorafenib, Sunitinib, Pazopanib on gastric cancer when used alone or in combination based on prospective clinical trials reported in the literature, and sorted response biomarkers. We also summarized the challenges faced by anti-angiogenesis therapy for gastric cancer and available solutions. Finally, the characteristics of the current clinical research are summarized and suggestions and prospects are raised. This review will serve as a good reference for the clinical research of anti-angiogenic targeted drugs in the treatment of gastric cancer.